Risk factors for bone metastasis in patients with primary lung cancer: A systematic review. Issue 3 (January 2019) - Niu, Yujie; Lin, Yiting; Pang, Hailin; Shen, Weiwei; Liu, Lili; Zhang, Helong
Abstract: Background: Bone metastases (BM) are prevalent among lung cancer (LC) patients. Although some studies revealed associated factors for BM, each of these papers focused on a few factors. Few studies have identified the potential risk factors through a systematic review. Methods: We searched through PubMed, MEDLINE, Web of Science, EMBASE, Cochrane Library and Cochrane Central Register of Controlled Trials for literature from January 1990 to November 2017. The types of literature included case–control studies, cohort studies, randomized controlled trials and systematic reviews. Results: From included 12 studies, we identified that lower blood calcium, T4 stage, N3 stage, P-stage III, nonsquamous, bone sialoprotein expression, elevated carcino-embryonic antigen levels were risk factors for bone metastasis in lung cancer patients. Conclusion: We identified that T4 stage, N3 stage, and positive bone sialoprotein expression associated with an increased risk of bone metastasis. Further studies are needed to assess these relationships and to establish the risk prediction model of bone metastasis. Abstract : Supplemental Digital Content is available in the text